The Epistemology of Riyāḍah in Pesantren: A Philosophical Foundation for Islamic Intellectual Formation - Fathurrohman, Rizal; Munip, Abdul; Achadi, Muh. Wasith (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2025)
This study examines how riyāḍah in the pesantren tradition is understood not only as a spiritual discipline but also as an epistemological foundation shaping the essence, sources, methods, and validation of knowledge. It arises from the need for a holistic and transformative paradigm of Islamic education beyond Western epistemology, often limited to rationalism and empiricism. The purpose is to explore the epistemology of riyāḍah in intellectual formation within Islamic education, with Pesantren Fathul ‘Ulum Kwagean, Kediri, East Java, as the research locus for its strong scholarly tradition and integration of spiritual discipline with intellectual development. The study employs qualitative research with an ethnographic approach to capture lived experiences and epistemological perspectives of the pesantren community. Data are obtained primarily from direct engagement with subjects as primary sources, complemented by secondary sources from classical Islamic texts. Data collection uses participant observation, in-depth interviews, and documentation. Analysis follows the Miles, Huberman, and Saldaña model, data collection, condensation, display, and conclusion drawing with verification. Validity is ensured through source triangulation. Findings show that in pesantren, knowledge is conceived as divine light attained through purification of the soul. Its sources and methods integrate texts, reason, empirical experience, and riyāḍah, while its validation rests on benefit and blessing. The significance of this research lies in its theoretical contribution to Islamic epistemology, its practical model for integrating spiritual discipline with intellectual formation, and its enrichment of Islamic education discourse by positioning riyāḍah as a foundation for both character building and knowledge production.